Screening innovative technologies for energy-efficient domestic hot water systems. (15th October 2022) - Hadengue, Bruno; Morgenroth, Eberhard; Larsen, Tove A.
Abstract: Domestic hot water systems are large energy consumers. With the aim of reducing the energy footprint of these systems, we selected and simulated five technologies across a wide range of technology readiness levels: established technologies – pipe insulation and low-flow faucets –, relatively new technologies – shower drain heat exchangers and an innovative pipe system – and a novel experimental technology – a heat exchanger connected to membrane bioreactor for on-site greywater treatment. Using the WaterHub modeling framework, we simulated the technologies alone and in combination and compared the energetic performance of fifteen scenarios with a validated reference domestic hot water system. Low-flow appliances as standalone technologies performed best with 30% less energy required for the boiler tank, but combining low-flow appliances with a membrane bioreactor heat exchanger performed best overall (50% reduction). Deep insights into the temperature dynamics at all locations in the system led to the identification of technological competition patterns to prevent and synergies to exploit. Through our results, we are able to discuss and recommend further investigations regarding critical aspects like hygiene and economic performance. Highlights: We assessed technologies to reduce the energy footprint of domestic hot water systems. Five technologies and their combinations were simulated with the WaterHub framework. Technology combinations can lead to competition or synergistic interactions. Dynamic simulations reveal underlying thermodynamic reasons for interactions. Concerns regarding hygiene should be recognized and critically assessed.